Real estate issues in Asia: An emerging paradigm - Hui, Eddie Chi‐man (International Journal of Strategic Property Management, 2010)
“Real estate issues in Asia: An emerging paradigm” International Journal of Strategic Property Management, 8(2), p. 59-61. First Published online: 18 Oct 2010